Combining molybdenum carbide with ceria overlayers to boost Mo/CeO2 catalyzed ammonia synthesis. Issue 11 (16th August 2022) - Fang, Biyun; Zhang, Chuanfeng; Qi, Zeliang; Li, Chunyan; Ni, Jun; Wang, Xiuyun; Lin, Jianxin; Au, Chak‐Tong; Lin, Bingyu; Jiang, Lilong
Abstract: The design of an efficient non‐noble metal catalyst is of burgeoning interest for ammonia synthesis. Herein, we report a Mo2 C/CeO2 catalyst that is superior in ammonia synthesis activity. In this catalyst, molybdenum carbide coexisted with the ceria overlayers which is from the ceria support as the strong metal–support interaction. There is a high proportion of low‐valent Mo species, as well as high concentration of Ce 3+ and surface oxygen species. The presence of Mo2 C and CeO2 overlayers not only leads to enhancement of hydrogen and nitrogen adsorption, but also facilitates the desorption and exchange of adsorbed species with the gaseous reagents. Compared with the Mo/CeO2 catalyst prepared without carbonization, the Mo2 C/CeO2 catalyst is more than sevenfold higher in ammonia synthesis rate. This work not only presents an explicit example of designing Mo‐based catalyst that is highly efficient for ammonia synthesis by tuning the adsorption and desorption properties of the reactant gases, but opens a perspective for other elements in ammonia synthesis.